Vial coring and fragmentation incidence after angled penetration of rubber stoppers with single-use hypodermic needles - Rase Marissa; Hanlon Mark; Ho Le; Duriez Doug; Zhao Cathy (De Gruyter, 2021)
Particles due to fragmentation present a clear risk to the patient. Reported fragmentation rates vary, and an insertion angle at 45°, as opposed to 90°, has been proposed as a mitigation strategy. So, this study evaluated the fragmentation rates induced by single-use hypodermic needles using different angled penetration techniques.